Feasibility and Potential Effects of Robot-Assisted Passive Range of Motion Training in Combination with Conventional Rehabilitation on Hand Function in Patients with Chronic Stroke - Chia-Yu Hsu; Chu-Ming Wu; Chieh-Cheng Huang; Hung-Hai Shie; Yuh-Show Tsai (Medical Journals Sweden, 2022)
Objective: To assess the effects of exoskeleton robot-assisted passive range of motion for induction training in combination with conventional hand rehabilitation in patients with chronic stroke. Design: Single-cohort feasibility study. Subjects: Chronic stroke with severe upper extremity hemiparesis. Methods: Thirty sessions of therapy over a period of 10 weeks. Each session started with 30 min robot-assisted passive range of motion for the hand, followed by 30 min conventional hand rehabilitation. The Fugl-Meyer Assessment for upper extremity, arm subscore of Motricity Index, Functional Independence Measure and Fugl-Meyer assessment for sensation (Fugl-Meyer assessment-sensory) were conducted at pre-intervention (pre) and after the 16th (16-post) and 30th (30-post) sessions of interventions. Results: Twelve patients with chronic stroke were recruited. The Fugl-Meyer assessment for upper extremity (16-post vs 30-post, p = 0.011), arm subscore of Motricity Index (pre vs 30-post, p = 0.012) and Functional Independence Measure (pre vs 30-post, p = 0.007; 16- post vs 30-post, p = 0.016) improved significantly after the therapy. However, FMA-sensory did not change significantly. Conclusion: Exoskeleton robot-assisted passive range of motion of the hand using an exoskeleton can be considered as an induction therapy before starting conventional therapy for hand rehabilitation in patients with chronic stroke. Further randomized control trials are needed to verify the therapeutic benefits. LAY ABSTRACT Motor recovery of hand dexterity is challenging during the chronic phase of stroke. Patients achieve different levels of hand function during the acute or subacute phase of stroke. Those receiving conventional physical therapy during the chronic phase of stroke usually experience difficulty in hand dexterity improvement after achieving motor recovery plateau. This pilot study investigated the effects of robot-assisted passive range of motion training in combination with conventional rehabilitation on hand function in a cohort of patients with chronic stroke who underwent follow-up at an outpatient rehabilitation clinic. The affected upper extremity function, strength and general function improved significantly after the therapy for the 12 patients recruited to this study. Using robot-assisted passive range of motion training as an induction therapy in combination with conventional rehabilitation may be beneficial for patients with chronic stoke who have impairment of hand function.